Signaling moral values through consumption - Florian H. Schneider (University of Zurich, Department of Economics, 2020)
Firms often discourage certain categories of individuals from buying their products, in contrast with typical assumptions about profit maximization. This paper provides a potential rationale for such firm behavior: consumers seek to signal that they have "good" moral values to themselves and others by avoiding products popular among people with "bad" values. In laboratory experiments, I provide causal evidence that demand for a product is lower if its customer base consists of individuals with undesirable moral values. This effect occurs for both observable and unobservable consumption and for products that do not possess any inherent moral or undesirable qualities.
Keywords: D12; C91; M3; 330; moral values; social image; self-image; signaling; consumption; experiments